Zur Rolle der Religion in der pakistanischen Staatskrise 1970/71 - Stietencron, Heinrich von (Internationales Asien-Forum, 1973)
One of the basic factors in the East Bengal conflict of 1971 was the existing religious and cultural difference between Bengali Muslims and the rest of Pakistani Muslims including „Biharis“. Due to a strong admixture of elements from Hinduism and folk-religion, Islam in Bengal has always been considered as impure by orthodox muslims. The stain of unorthodoxy resulted socially and morally in a slight degradation of Bengalis, including their upper class members. This affected the position of Bengal in Pakistan and provoked resentment among Bengalis against West-Pakistanis and specially against Biharis. From the side of the orthodox muslim community, a call for purging out the Hindu elements has been repeated again and again since the 17th century. The Hindus were undermining Islam and continued to be a threat to the islamic state. The Army action against Hindus in East Bengal took advantage of these tensions. Its objective was to eliminate a danger to Islam, and a danger to the state.